Pelaksanaan Pembelajaran Berbasis Masalah untuk meningkatkan Hasil Belajar IPA di Kelas V SDN 02 Silaut Kecamatan Silaut Kabupaten Pesisir Selatan - Zuldia Darman (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2018)
This research is motivated by science learning which is still teacher-centered. So that boring science learning takes place. Besides that, the standard of completeness in the desired science learning has not been achieved. The purpose of this study is to improve student learning outcomes by using Action Research through problem-based learning strategies which include (1) planning, (2) implementation, and (3) learning outcomes. Based on the results of the study, it appears that student learning outcomes have increased. By using problem-based learning strategies, the percentage of the results of the average value of student learning in the first cycle was 66.97% and in the second cycle the percentage of students' average score was 82.26%. The percentage increase in the average value of the results of the first cycle and second cycle is 5.29%. The conclusion of this study is to use problem-based learning strategies to improve learning outcomes of class V students of SDN 02 Silaut.